Lactoferrin-modified rotigotine nanoparticles for enhanced nose-to-brain delivery: LESA-MS/MS-based drug biodistribution, pharmacodynamics, and neuroprotective effects - Yan X; Xu L; Bi C; Duan D; Chu L; Yu X; Wu Z; Wang A; Sun K (International Journal of Nanomedicine, 2018)
Xiuju Yan,1,* Lixiao Xu,1,* Chenchen Bi,1 Dongyu Duan,1 Liuxiang Chu,1 Xin Yu,1 Zimei Wu,1 Aiping Wang,1,2 Kaoxiang Sun1,2 1School of Pharmacy, Collaborative Innovation Center of Advanced Drug Delivery System and Biotech Drugs in Universities of Shandong, Key Laboratory of Molecular Pharmacology and Drug Evaluation (Yantai University), Ministry of Education, Yantai University, Yantai, Shandong Province, 2State Key Laboratory of Long-Acting and Targeting Drug Delivery System, Shandong Luye Pharmaceutical Co., Ltd, Yantai, Shandong Province, People’s Republic of China *These authors contributed equally to this work Introduction: Efficient delivery of rotigotine into the brain is crucial for obtaining maximum therapeutic efficacy for Parkinson’s disease (PD). Therefore, in the present study, we prepared lactoferrin-modified rotigotine nanoparticles (Lf-R-NPs) and studied their biodistribution, pharmacodynamics, and neuroprotective effects following nose-to-brain delivery in the rat 6-hydroxydopamine model of PD.Materials and methods: The biodistribution of rotigotine nanoparticles (R-NPs) and Lf-R-NPs after intranasal administration was assessed by liquid extraction surface analysis coupled with tandem mass spectrometry. Contralateral rotations were quantified to evaluate pharmacodynamics. Tyrosine hydroxylase and dopamine transporter immunohistochemistry were performed to compare the neuroprotective effects of levodopa, R-NPs, and Lf-R-NPs.Results: Liquid extraction surface analysis coupled with tandem mass spectrometry analysis, used to examine rotigotine biodistribution, showed that Lf-R-NPs more efficiently supplied rotigotine to the brain (with a greater sustained amount of the drug delivered to this organ, and with more effective targeting to the striatum) than R-NPs. The pharmacodynamic study revealed a significant difference (P<0.05) in contralateral rotations between rats treated with Lf-R-NPs and those treated with R-NPs. Furthermore, Lf-R-NPs significantly alleviated nigrostriatal dopaminergic neurodegeneration in the rat model of 6-hydroxydopamine-induced PD.Conclusion: Our findings show that Lf-R-NPs deliver rotigotine more efficiently to the brain, thereby enhancing efficacy. Therefore, Lf-R-NPs might have therapeutic potential for the treatment of PD. Keywords: lactoferrin-modified rotigotine nanoparticles, nose to brain, drug biodistribution, pharmacodynamics, neuroprotective effects, Parkinson’s disease